Associations of periodontal status in periodontitis and rheumatoid arthritis patients - Rovas, Adomas (J Periodontal Implant Sci, 2021)
PURPOSE: The aim of this study was to assess the association between the clinical status of rheumatoid arthritis (RA) and periodontitis (PD) in patients diagnosed with PD and to evaluate the impact of RA treatment on the severity of PD. METHODS: The study included 148 participants with PD, of whom 64 were also diagnosed with RA (PD+RA group), while 84 age-matched participants were rheumatologically healthy (PD-only group). PD severity was assessed by the following periodontal parameters: clinical attachment loss, probing pocket depth (PPD), bleeding on probing (BOP), alveolar bone loss, and number of missing teeth. RA disease characteristics and impact of disease were evaluated by the Disease Activity Score 28 using C-reactive protein, disease duration, RA treatment, the RA Impact of Disease tool, and the Health Assessment Questionnaire. Outcome variables were compared using parametric and non-parametric tests and associations were evaluated using regression analysis with the calculation of odds ratios (ORs). RESULTS: Participants in the PD+RA group had higher mean PPD values (2.81 ± 0.59 mm vs. 2.58 ± 0.49 mm, P=0.009) and number of missing teeth (6.27±4.79 vs. 3.93±4.08, P=0.001) than those in the PD-only group. A significant association was found between mean PPD and RA (OR, 2.22; 95% CI, 1.16–4.31; P=0.016). Within the PD+RA group, moderate to severe periodontal disease was significantly more prevalent among participants with higher RA disease activity (P=0.042). The use of biologic disease-modifying antirheumatic drugs (bDMARDs) was associated with a lower BOP percentage (P=0.016). CONCLUSIONS: In patients with PD, RA was associated with a higher mean PPD and number of missing teeth. The severity of PD was affected by the RA disease clinical activity and by treatment with bDMARDs, which were associated with a significantly lower mean BOP percentage.